Diagnosis of Unusual Protruding Type Thrombus on Left Ventricle Free Wall in Labrador Retriever Dogs - Sangwan, Tanvika; Saini, Neetu; Kataria, Deepika (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Canine cardiac diseases have an incidence of 10-15 %, out of which the acquired cardiac diseases like valvular diseases and dilated cardiomyopathy (DCM) have most common occurrence. Geriatric male Labrador retriever dogs are most commonly affected from DCM like cardiac disorders (Hoque et al., 2019). Intra-cardiac thrombi and thromboembolism are very unusual in dogs in comparison to the continual complication of cardiomyopathies in cats (Fuentes, 2012). As in humans where left ventricular thrombosis is considered to be a dreadful complication of ischemic heart diseases like myocardial infarction (Nixon, 1983), but, according to Virchow’s triad of thrombosis various heart diseases affecting left atrial and ventricle functioning, myocardial contractility pose a higher risk for thrombus formation in dogs (Watson et al., 2009; Usechak et al., 2012). Very few case reports on intra-cardiac thrombi are reported in dogs and only one study reported the presence of thrombus in left ventricle of dogs which was attached to inter-ventricular septum (Caivano et al., 2014). The perusal of the literature revealed that various studies have reported the left ventricular wall thrombosis as a complication of primary heart diseases in humans (Thuny et al., 2006; Ye et al., 2018), but no reports are available in veterinary literature depicting the presence of protruding thrombus on the left ventricle free wall of dogs. So, this is the first report of left ventricular wall thrombosis arising as a complication of concurrent DCM in two Labrador dogs.
Keywords: Diagnosis; Unusual Protruding; Thrombus; Retriever Dogs